2021
DOI: 10.1177/10870547211050949
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Effects of Cannabis on ADHD Symptoms, ADHD Medication Side Effects, and ADHD-Related Executive Dysfunction

Abstract: Objective: People with ADHD are more likely to use cannabis but little is known about the effects of cannabis on ADHD symptoms, ADHD medication side effects, or ADHD-related executive dysfunction. Method: Students ( n = 1,738) completed an online survey containing measures of ADHD symptoms, cannabis use, perceived effects of cannabis on ADHD symptoms and medication side effects, as well as executive dysfunction. Results: Participants with ADHD who have used cannabis reported that cannabis has acute beneficial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 73 publications
(109 reference statements)
1
17
2
1
Order By: Relevance
“…In previous studies of patients who self-medicate a health condition with cannabis, proportions of patients who reported the use of products with high doses of THC were also high (Sexton et al 2016 ; Turna et al 2020 ; Stueber and Cuttler 2022 ). In a study of students who mostly use cannabis to self-medicate their ADHD symptoms, the use of products with high THC/low CBD was reported by 41% of participants while 24% reported use of high THC/high CBD products (Stueber and Cuttler 2022 ). The use of products with THC concentration > 20% was reported by 27% of this study’s participants (Stueber and Cuttler 2022 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In previous studies of patients who self-medicate a health condition with cannabis, proportions of patients who reported the use of products with high doses of THC were also high (Sexton et al 2016 ; Turna et al 2020 ; Stueber and Cuttler 2022 ). In a study of students who mostly use cannabis to self-medicate their ADHD symptoms, the use of products with high THC/low CBD was reported by 41% of participants while 24% reported use of high THC/high CBD products (Stueber and Cuttler 2022 ). The use of products with THC concentration > 20% was reported by 27% of this study’s participants (Stueber and Cuttler 2022 ).…”
Section: Discussionmentioning
confidence: 95%
“…In a study of students who mostly use cannabis to self-medicate their ADHD symptoms, the use of products with high THC/low CBD was reported by 41% of participants while 24% reported use of high THC/high CBD products (Stueber and Cuttler 2022 ). The use of products with THC concentration > 20% was reported by 27% of this study’s participants (Stueber and Cuttler 2022 ). Turna et al also observed in a Canadian sample that products with high THC concentration were reported to be used by 32% of the study participants, with the highest proportion observed among mixed cannabis users (Turna et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…From a neurobiological perspective, treatment by stimulants reduces the use of substance abuse in persons with ADHD [ 63 , 64 ], consistent with the self-medication hypothesis [ 65 ]. Indeed, some studies report results suggesting that the use of cannabis could reduce ADHD symptoms [ 66 70 ]. In addition, in students with ADHD, cannabis use is a moderator of ADHD symptoms severity—executive dysfunction relationship and is linked with a reduction of their perceived medications’ side effects [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some studies report results suggesting that the use of cannabis could reduce ADHD symptoms [66][67][68][69][70]. In addition, in students with ADHD, cannabis use is a moderator of ADHD symptoms severity-executive dysfunction relationship and is linked with a reduction of their perceived medications' side effects [66]. From a cognitive perspective, a deficit in executive functions such as planning and response inhibition is particularly linked with ADHD [71].…”
Section: Comparison With Other Studies and Interpretationmentioning
confidence: 99%
See 1 more Smart Citation